Service-based data storage and retrieval framework for smart cities - De Barros Corrêa, Felipe Pavan [UNESP]; Marçal, Ingrid [UNESP]; Garcia, Rogério Eduardo [UNESP]; Junior, Celso Olivete [UNESP]; Eler, Danilo Medeiros [UNESP]; Correia, Ronaldo Celso Messias [UNESP] (My University, 2020)
With population growth and the increasing use of technologies, making Smart Cities is fundamental for improving the population’s quality of life, one characteristic that this brings is the generation of a large volume of data. In this context it was developed the Smart Cities Service Framework, a framework to generate classes for storing and retrieving data structured and unstructured, using Web Services. Experiments were performed at different comparative edges, and the results obtained indicate that the use of Web Services to access the databases is a good alternative, according to the benefits that the use of this technology brings as interoperability, cost reduction, freedom of implementation, security, and others.
Framework para armazenamento e recuperação de dados baseado em serviços para cidades inteligentes
Keywords: Database; Smart cities; Web services